Comercialización de maíz amarillo duro y su relación con la soberanía alimentaria de la federación provincial de organizaciones comunitarias “tierra fértil”, cantón Ventanas, periodo 2014. - Escobar Guananga, Yomaira Lisette (2015)
This study was conducted in the Ventanas Canton and its surroundings; it involved the main actors of the Provincial Federation of Community Organizations "Fertile Ground" in the period 2014, 175, members through a questionnaire and an interview with its CEO, as Chairman Mr. Roman Andrade Gerardo Ortiz. Very important is the knowledge of the agricultural sector producing yellow corn, where the main problem is the marketing thereof; However this, should not be left to note that those involved, suffering from the beginning of pre sowing, planting, maintenance and harvest survey, always have insurmountable problems; at this, the founders, at number 22, formed an organization that defends the interests of small and medium producers and is known later as FEPROCTIFE and currently at number 175 members of various community organizations, are part of thereof. The institution is concerned to ensure the marketing of yellow corn, priced official support, which among others has the qualification and just weight; as well as timely payments. At the same time the agreements signed with government agencies ensure the sustainability of Sovereignty and Food Safety, as the main axis of the matrix Productive change advocated by the Central Government. To develop inductive-deductive research method was used, which allowed collecting information of qualitative and quantitative research, based on direct observation of the facts, based on the survey, to arrive at the interpretation of the results and conclusion that there is an institutional commitment to its members. The organization is committed to supporting its members in all matters relating to the financing of the initiative associate producer with quality seeds, inputs and technical advice, so that contribute to strengthening partnerships with government agencies to Productive consolidate Matrix, ensuring food sovereignty and security, one of the strategic sectors of the same. Research concludes with the important contribution regarding the sovereignty, security and productive matrix, as a philosophy of change implemented by the central government, the same that involves all stakeholders in production.